REPOSITIONING CULTURE IN TEACHING TARGET LANGUAGE: LOCAL CULTURE OR TARGET CULTURE? - Hieronimus Canggung Darong; Sebastianus Menggo (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2021)
The role of culture in teaching target language is undeniable. This article belongs to a literature review. As such, it deals with the reviews of culture integration in English Language Teaching. The article provides the conflicting findings of teaching target language with local culture or target culture along with the reasonable reasons for each. The writers adopt the systematic way of doing literature review consisting of four steps namely designing the review, conducting the review, analyzing, and writing the review. Drawing from the review of the progress reports in the field, the writer recommends an intermediary for prospective English Language Teaching accommodating both local and target culture in question. Recommendations for future research studies are highlighted at the end.